2017
DOI: 10.18632/oncotarget.16740
|View full text |Cite
|
Sign up to set email alerts
|

Gastrodin protects against LPS-induced acute lung injury by activating Nrf2 signaling pathway

Abstract: Gastrodin (GAS), a phenolic glucoside derived from Gastrodiaelata Blume, has been reported to have anti-inflammatory effect. The aim of this study was to investigate the effects of GAS on LPS-induced acute lung injury in mice. ALI was induced by the intranasal administration of LPS and GAS was given 1 h or 12 h after LPS treatment. The results indicated that GAS treatment markedly attenuated the damage of lung injury induced by LPS. GAS attenuated the activity of myeloperoxidase (MPO) and down-regulated the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…25 gastrodin may even attenuate LPS-induced acute lung injury. 10 Thus, it seems rationality that gastrodin could also protect MRC-5 cells against…”
Section: Discussionmentioning
confidence: 99%
“…25 gastrodin may even attenuate LPS-induced acute lung injury. 10 Thus, it seems rationality that gastrodin could also protect MRC-5 cells against…”
Section: Discussionmentioning
confidence: 99%
“…4-HBA and β-gastrodin are the main phenolic constituents of GE [16]. They reduce oxidative stress by upregulating Nrf2 [17,18]. β-Gastrodin downregulated IL-6 and MAPKs [6].…”
Section: Effect Of Ege's Active Components On Mmp-1 Mmp-3 and Procomentioning
confidence: 99%
“…Gastrodin, a major active ingredient of Chinese herbal medicine called Gastrodia elata Blume, has been reported to exert anti-inflammatory and anti-apoptotic effects in various diseases (10,11). Importantly, Peng et al (12) found gastrodin treatment reduced reactive oxygen species production in macrophages and protected macrophages against oxidative stress-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%